STRATEGIC OPTIMIZATION OF CASH WAQF IN INDONESIA, A PRODUCTION FUNCTION AND GOVERNANCE-BASED APPROACH - Jaharuddin Jaharuddin (Multidisciplinary Research Studies in Social Sciences, 2025)
Cash waqf (waqf al-nuqud) has emerged as a dynamic instrument within the broader framework of Islamic social finance, offering a flexible, inclusive, and potentially high-impact mechanism for sustainable development in Muslim-majority societies. Despite its significant potential—particularly in countries like Indonesia, where the annual estimated cash waqf capacity exceeds IDR 180 trillion—its realization remains suboptimal due to limitations in governance, institutional professionalism, and public trust. This study aims to develop a conceptual model for optimizing cash waqf management in Indonesia by integrating Islamic jurisprudential principles, behavioral economics, and production theory. Utilizing a qualitative, literature-based approach, the research synthesizes theoretical insights with practical models such as Interpretive Structural Modeling (ISM), SWOT analysis, and case studies from Indonesia (Waqf Amerta) and Malaysia (ICWME-I). A simplified production function model—WT=f(P,N)WT = f(P, N)—is proposed, where cash waqf output (WT) is determined by waqf potential (P) and the professionalism of nazhir institutions (N). Findings highlight that strategic optimization of cash waqf requires a multi-level approach involving regulatory reforms, human capital development, institutional transparency, and systematic public engagement. The study advocates for the establishment of professional nazhir institutions modeled after financial industry standards, with active state support in education, certification, and governance. By bridging theoretical and practical dimensions, this paper contributes to the growing literature on Islamic philanthropic finance and offers a strategic framework for enhancing the role of cash waqf as a vehicle for inclusive socio-economic transformation.Keywords: Cash Waqf; Islamic Social Finance; Nazhir Professionalism; Production Theory; Waqf Optimization; Strategic Modeling; Good Waqf Governance